PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. NATIONAL LABEL KABUPATEN TANGERANG - Maulana, Azhar; Syamsuddin, Rahmi Andini (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of leadership style and work environment on employee performance at PT National Label Tangerang Regency. The method used is quantitative. The sampling technique used saturated sampling with population and a sample of 80 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that leadership style has a significant effect on employee performance with a coefficient of determination value of 38.8% and the hypothesis test obtained t count > t table or (7.029 > 2.000). The work environment has a significant effect on employee performance with a coefficient of determination value of 70.3% and the hypothesis test obtained t count > t table or (13,772 > 2,000). Leadership style and work environment simultaneously have a significant effect on employee performance with the regression equation Y = 2.989 + 0.109 X1 + 1.023 X2. The coefficient of determination value is 71.3% while the remaining 28.7% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (95.415 > 2.700).